Penurunan Waktu Changeover dengan Metode SMED di PT.Schneider Electric Manufacturing Batam-Plant Electro Mechanic - Sudargo, Kristianto Wibowo; felecia, felecia (Jurnal Titra, 2015)
PT Schneider Electric Manufacturing Batam-Plant Electro Mechanic is a company that produce electrical parts. Changeover time on some bench in production floor are very high, Thatâs why it needs to be reduced and improved. The method that will be used are Single Minutes Exchange of Dies (SMED) This project started with observing all machine on production floor, and after that some machine will be chosen to be improved. Changeover time data will be taken from this chosen machine, and this data will be analyzed with SMED. The result from SMED data will become suggested improvement for each machine. Suggested improvement that able to straightly be done will be directly implemented to target machine.Improvement on bench Auto Tampo Print was able to reduce the changeover time by 47%. Estimate improvement on bench Printing Body XB7-2nd Life should be able to reduce the changeover time by 75%. Estimate improvement on bench Manual Checker should be able to reduce the changeover time by 44%. Estimate improvement on bench Coil Winding and Testing MARSILI should be able to reduce changeover time by 18%. Estimate improvement on bench Coil Winding DETZO should be able to reduce changeover time by 7.4%.